The house of Kennedy - Patterson, James (New York Hachette Audio, 2020)
The Kennedys have always been a family of charismatic adventurers, raised to take risks and excel, living by the dual family mottos: "To whom much is given, much is expected" and "Win at all costs." And they do--but at a price.
Keywords: .